The Role of Diffusion Weighted MRI in Differentiation of Malignant from Benign Ovarian Tumors - Rashidzadeh, Mehri; Haghighatkhah, Hamidreza; Farzaneh, Farahnaz; Barfei, Mandana (Student Research in Translational Medicine, 2021)
Introduction: Ovarian masses are common and due to the risk of dissemination, biopsy is not recommended before surgery; thus, imaging techniques can play a crucial role in differentiating benign from malignant lesions. Diffusion weighted magnetic resonance imaging (DW-MRI) is now considered a part of the standard evaluation of pelvis. The aim of this study was to investigate the role of DW-MRI in distinguishing between benign and malignant ovarian tumors and its comparison with pathology results. Materials and Methods: In this descriptive analytic study, 85 non-pregnant women of childbearing age with an ovarian mass who were referred to Imam Hossein hospital in 2018 were evaluated. All patients underwent MRI before surgery and apparent diffusion coefficient (ADC) value was calculated for each. In addition, demographic data and postoperative pathology results were recorded. The acquired data were then entered into the SPSS software for statistical analysis. Results: The mean age of the participants was 39.01 ± 6.98 years. Mean ADC value was calculated as 1.14 ± 0.67 × 10-3 mm2/s. Mean ADC value was significantly lower in malignant lesions compared to borderline and benign ones (P<0.001). There was a significant inverse relationship between ADC values and malignancy (r= -0.841, P<0.001); the higher the ADC value, the lower the probability of malignancy. Mean ADC value was the highest in cysts and the lowest in metastatic lesions (with the exception of serous cystadenocarcinoma (P=0.267) compared to other types of lesions (P<0.05). The optimal cutoff point for ADC to differentiate between benign and malignant ovarian lesions was 1.16 × 10-3 mm2/s with 95% sensitivity, 100% specificity, 100% positive predictive value (PPV), 98% negative predictive value (NPV), and 99% accuracy. Conclusions: ADC value in DW-MRI is highly sensitive and specific in differentiation between benign and malignant ovarian tumors.